2012
DOI: 10.1016/j.jse.2011.05.004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tear size and nerve injury on rotator cuff muscle fatty degeneration in a rodent animal model

Abstract: Background Irreversible muscle changes following rotator cuff tears is a well-known negative prognostic factor after shoulder surgery. Currently, little is known about the pathomechanism of fatty degeneration of the rotator cuff muscles after chronic cuff tears. Hypothesis/Purpose The purposes of this study were: 1) to develop a rodent animal model of chronic rotator cuff tears that can reproduce fatty degeneration of the cuff muscles seen clinically, 2) to describe the effects of tear size and concomitant n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
158
1
11

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(190 citation statements)
references
References 37 publications
20
158
1
11
Order By: Relevance
“…Although we are aware of no human rotator cuff data regarding gene expression markers of adipogenesis, some data are available in animals. These data suggest similar trends to those observed in our study, although the relative differences between injured and control animals were much smaller and appear to be related to the addition of neurotomy 38 . The family of genes related to fibrosis showed evidence of profibrotic activity in the tendinopathy group (COL3A1, TIMP1, and TIMP3).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although we are aware of no human rotator cuff data regarding gene expression markers of adipogenesis, some data are available in animals. These data suggest similar trends to those observed in our study, although the relative differences between injured and control animals were much smaller and appear to be related to the addition of neurotomy 38 . The family of genes related to fibrosis showed evidence of profibrotic activity in the tendinopathy group (COL3A1, TIMP1, and TIMP3).…”
Section: Discussionsupporting
confidence: 89%
“…This has been observed previously in human subjects with rotator cuff tears 35 , although the expression data presented here indicate a much greater ratio between muscles with a massive tear and less severe injury states as well as a more obvious effect when massive tears are compared with full-thickness tears. Similarly, upregulation of MSTN has been observed previously in animal models of rotator cuff injury, although the relative change compared with controls was extremely small 38 .…”
Section: Discussionsupporting
confidence: 70%
“…4 Recent rat models of massive RCTs have used a 5-mm tendon defect to successfully show muscle atrophy and fatty infiltration of the injured muscle. 32,33 Two studies in rats have shown that simultaneous suprascapular nerve injury and massive RCTs have significantly increased the amounts of fatty infiltration and muscle atrophy. 32,33 Interestingly, Rowshan et al 42 reported that isolated neurologic injury in rabbits produces fatty infiltration that is phenotypically comparable to that in those undergoing massive RCTs.…”
Section: Animal Models Of Rctsmentioning
confidence: 99%
“…With respect to the molecular mechanism underlying muscle fat accumulation, it has been reported that pluripotent stem cells or progenitor cells residing in the muscle differentiate into adipocytes by the action of adipogenic transcription factors such as CCAAT/enhancer binding protein alpha (C/EBPα) and peroxisome proliferator activated receptor gamma (PPARÎł) 8, 21, 22. Previous studies have suggested that rotator cuff fatty infiltration is also mediated by these adipogenic transcription factors 8, 23, 24, 25. However, considering the population of stem cells available at old age, it is possible that other regulators are also involved in intramuscular fat accumulation.…”
Section: Introductionmentioning
confidence: 99%